O trabalho como princípio educativo na proposta educativa e escolar de Moisey Pistrak: contribuições para a educação na atualidade - Cruz, Marilei Leal da (2022)
This research is part of the Research Line Society, Knowledge and Education, of the Postgraduate Program in Education (PPGE, acronym in Portuguese) of the State University of Oeste do Paraná (Unioeste), Francisco Beltrão campus (PR). The chosen object of study was work as an educational principle in the school proposal of Moisey Mikhaylovich Pistrak (1888- 1937), a Soviet educator who worked during the Russian revolutionary period (1917-1931). The general objective was to analyze labor as an educational principle in Moisey Pistrak's educational and school proposal, situating its contributions to education today. The specific goals, in turn, were: (i) to investigate the theoretical assumptions that guided the development of Moisey Pistrak's educational proposal; (ii) to conceptualize and analyze the main pedagogical categories elaborated by Pistrak in the experiences of the Commune Schools, which materialized labor as an educational principle of education; and (iii) to understand and analyze how the school experience coordinated by Pistrak in the Commune Schools contributes to an understanding of labor as an educational principle today. The research, of a qualitative approach, was based on Historical-Dialectical Materialism. The methodological path was composed of bibliographic research and document analysis. The results indicated that the Soviet educators taught us that pedagogical practice must be linked to the struggle for the transformation of today, based on the self-organization of students and the working class, connected to socially useful work. Thus, based on Pistrak's proposal, it is possible to conclude that in order to build a new perspective for the relationship between labor, education, and teaching, it is necessary to obligatorily incorporate labor as an educational principle in the educational process, through the most varied forms of socially productive labor. All of this should be articulated to a critical reading of current events, to the exercise of self-management and self-organization by the students, having as a final objective a polytechnic and multilateral formation. Precisely because of this, socialist pedagogy is capable of opposing the pedagogy of the capital, contributing significantly to the overcoming of capitalism and its capitalist school form.